2023
DOI: 10.17925/hi.2023.17.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Prediabetes Compared with Normoglycaemia and Diabetes Mellitus in Patients Undergoing Percutaneous Coronary Intervention: A Systematic Review and Meta-analysis

Muhammad Junaid Ahsan,
Azka Latif,
Soban Ahmad
et al.

Abstract: Background: Patients with prediabetes are at increased risk of coronary artery disease (CAD). However, the association between prediabetes and adverse clinical outcomes following percutaneous coronary intervention (PCI) is inconsistent, in contrast to outcomes in patients with diabetes mellitus (DM). Thus, this meta-analysis evaluated the impact of dysglycaemia on PCI outcomes. Methods: The PubMed, Embase, Cochrane, and ClinicalTrials. gov databases were systematically reviewed from inception of databases unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A recent meta‐analysis of 17 studies demonstrated that the risks of all‐cause mortality, MI, and cardiac mortality were lower in the NG compared to the prediabetic patients at the longest follow‐up, with the mean of the follow‐up periods of the studies being 2.6 years. Moreover, patients with prediabetes had a lower risk of all‐cause mortality and cardiac mortality compared to patients with diabetes 18 . In the HEART2D trial, patients with type 2 diabetes following PCI were randomized to receive prandial versus basal insulin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent meta‐analysis of 17 studies demonstrated that the risks of all‐cause mortality, MI, and cardiac mortality were lower in the NG compared to the prediabetic patients at the longest follow‐up, with the mean of the follow‐up periods of the studies being 2.6 years. Moreover, patients with prediabetes had a lower risk of all‐cause mortality and cardiac mortality compared to patients with diabetes 18 . In the HEART2D trial, patients with type 2 diabetes following PCI were randomized to receive prandial versus basal insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with prediabetes had a lower risk of all‐cause mortality and cardiac mortality compared to patients with diabetes. 18 In the HEART2D trial, patients with type 2 diabetes following PCI were randomized to receive prandial versus basal insulin. MACE did not differ between the groups at 1 year (11.0% vs. 12.3%, p = .33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations